1981
DOI: 10.1128/jvi.39.3.914-919.1981
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and immunological comparison of caprine arthritis encephalitis and ovine progressive pneumonia viruses

Abstract: Caprine arthritis encephalitis virus (CAEV) causes a variety of pathological conditions ranging from mild to very severe and from acute to chronic, depending upon the age of initial infection and other variables. Although the virus has been reported to have properties characteristic of retroviruses and to be related to maedi-visna virus (also called progressive pneumonia virus [PPV]), relatively little information about its morphological and immunological characteristics has been reported. We describe the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 15 publications
4
18
0
2
Order By: Relevance
“…The present analysis of the protein content of both types of viruses demonstrated that highly lytic viruses [OMVV(I)] are closely related in terms of structure to the prototype strains of Icelandic visna virus (K796 and K1514) and American PPV (strain Kennedy), whereas the persistent virus [OMVV(II)] is very similar to the American strain of CAEV. As previously shown in serological studies of visna virus and CAEV (7,20,26), type I and type II ovine lentiviruses share common antigenic determinants in their major internal protein, p30, and major envelope glycoprotein, gp135. In contrast, smaller internal proteins [p16 and p14 for OMVV(I); p18 and p14.5 for OMVV(II) and CAEV)] do not seem to share major antigenic determinants.…”
Section: P3-supporting
confidence: 52%
See 1 more Smart Citation
“…The present analysis of the protein content of both types of viruses demonstrated that highly lytic viruses [OMVV(I)] are closely related in terms of structure to the prototype strains of Icelandic visna virus (K796 and K1514) and American PPV (strain Kennedy), whereas the persistent virus [OMVV(II)] is very similar to the American strain of CAEV. As previously shown in serological studies of visna virus and CAEV (7,20,26), type I and type II ovine lentiviruses share common antigenic determinants in their major internal protein, p30, and major envelope glycoprotein, gp135. In contrast, smaller internal proteins [p16 and p14 for OMVV(I); p18 and p14.5 for OMVV(II) and CAEV)] do not seem to share major antigenic determinants.…”
Section: P3-supporting
confidence: 52%
“…USA-CAEV induces a persistent infection of goat cells without resulting in complete cell lysis as in maedi-visna virus infections (18,20). It shares with maedi-visna viruses p30 and gp135-related antigens (4, 26) but contains internal proteins, smaller than p30, which are probably antigenically distinct from maedivisna viruses p16 and p14 (7). USA-CAEV and Icelandic visna virus have in common only 20 to 30% of their nucleic acid sequences (11,26).…”
mentioning
confidence: 99%
“…Retention of virus within macrophages is not novel for retroviruses. Other lentiviruses, such as caprine arthritis encephalitis and ovine progressive pneumonia virus also bud into and accumulate in cytoplasmic vacuoles (27,28) . These viruses have strong tropism for blood monocytes or tissue macrophages, yet viral replication is restricted and entirely dependent upon host cell (macrophage) differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…However, isolation of BIV may not always be possible. Precipitating antibodies could not be demonstrated with BIV antigens, in contrast to caprine arthritis encephalitis virus (CAEV), equine infectiousanaemia-virus (EIAV) and maedi-visna-virus (MVV) antigens (COGGINS and NORCROSS, 1970;CRAWFORD et al, 1980;NARAYAN et al, 1980;DAHLBERG et al, 1981;BOUILLANT et al, 1989). The seroprevalence of BIV in the cattle population in many countries, including Germany, is at present unknown.…”
Section: Introductionmentioning
confidence: 99%